Rethinking the Optimal Duration of Immune Checkpoint Inhibitors in Non-small Cell Lung Cancer Throughout the COVID-19 Pandemic - Friedlaender, Alex; Kim, Chul; Addeo, Alfredo (Frontiers in Oncology, 2020)
Immune checkpoint inhibitors (ICPIs) have revolutionized the management and prognosis of fit patients with advanced non-small cell lung cancer (NSCLC). Recently, the publication of 5-year survival rates has cemented the role of ICPIs in NSCLC. An ongoing challenge is to determine the optimal treatment duration to find the balance between efficacy, toxicity and cost. From the onset of ICPI trials, different durations were used, ranging from treatment until progression or toxicity, to fixed durations of 2 years. Subsequently, exploratory analyses from a 1-year fixed duration trial failed to change practice. There are, to date, no adequately powered prospective trials addressing this important question. With today's severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) pandemic, more than ever, the question resurfaces with added factors tilting the already shaky therapeutic balance. Here, we will discuss current data regarding ICPI treatment duration and incorporate this into the context of the ongoing pandemic. We conclude with a discussion of pragmatic approaches, should physicians be unable to continue standard therapy.